Age‐related decline of interferon‐gamma responses in macrophage impairs satellite cell proliferation and regeneration. Issue 5 (29th July 2020) - Zhang, Congcong; Cheng, Naixuan; Qiao, Bokang; Zhang, Fan; Wu, Jian; Liu, Chang; Li, Yulin; Du, Jie
Abstract : Background: Impaired muscle regeneration and increased muscle fibrosis are observed in aged muscle accompanied by progressive loss of muscle mass (sarcopenia). However, the underlying mechanism is still unclear. Methods: The differentiated expressed genes in young and aged muscles after acute injury by cardiotoxin were identified by RNA‐sequence analysis. Single‐cell RNA‐sequence analysis was used to identify cell clusters and functions in young muscle after acute injury, and flow cytometry analysis and sorting were used to validate the function. The proliferation and differentiation functions of satellite cells were accessed by immunostaining with 5‐ethynyl‐2′‐deoxyuridine and embryonic myosin heavy chain (eMyHC), respectively. Muscle regeneration ability was accessed by histopathological and molecular biological methods. Results: Gene expression patterns associated with responses to interferon‐gamma (IFN‐γ) (15 genes; false discovery rate < 0.001) were significantly down‐regulated during muscle regeneration in aged mice ( P  = 2.25e−7). CD8 + T cells were the main source of increased IFN‐γ after injury, adoptive transfer of wild‐type CD8 + T cells to IFN‐γ‐deficient young mice resulted in 78% increase in cross‐sectional areas (CSAs) of regenerated myofibres ( P  < 0.05) and 63% decrease in muscle fibrosis ( P  < 0.05) after injury. Single‐cell RNA‐sequence analysis identified a novel subset of macrophages [named as IFN‐responsive macrophages (IFNRMs)] that specifically expressed IFN‐responsive genes ( Ifit3, Isg15, Irf7, etc.) in young mice at 3 days after injury, and the number of this macrophage subset was ~20% lower in aged mice at the same time ( P  < 0.05). IFNRMs secreted cytokine C‐X‐C motif chemokine 10 (CXCL10) that promoted the proliferation and differentiation of satellite cells via its receptor, CXCR3. Intramuscular recombinant CXCL10 treatment in aged mice rejuvenated the proliferation of satellite cells (80% increase in Ki‐67 + Pax7 + cells, P  < 0.01) and resulted in 27% increase in CSA of regenerated myofibres ( P  < 0.01) and 29% decrease in muscle fibrosis ( P  < 0.05). Conclusions: Our study indicates that decline in IFN‐γ response in a novel subset of macrophage contributes to satellite cells dysfunctions in aged skeletal muscles and demonstrates that this mechanism can be targeted to restore age‐associated myogenesis.